DESKRIPSI KESULITAN BELAJAR SISWA SMA PADA MATERI STOIKIOMETRI - Sakti, Lusy Ela (RC-INSTITUT, 2018)
Stoichiometry is a material learned by high school students in class X even semester. In this material, 91.44% of students in SMAN 4 Kerinci at class X MIPA have not been able to achieve the minimum completeness criteria set. This case indicates that students experience learning difficulties. Learning difficulties are failures in achieving learning goals that are characterized by low learning outcomes. This research is a descriptive study that aims to determine the percentage of students' learning difficulties in stoichiometry material and find out the factors causing student learning difficulties internally. The subjects of this study were students of class XI MIPA 2 SMAN 4 Kerinci. The research instruments used were description tests, questionnaires and interviews. For data analysis used descriptive analysis. The results of this study, to show that students of SMAN 4 Kerinci have learning difficulties in stoichiometric material with a very high category. The highest level of student learning difficulties is found in indicator 9, which determines the amount of substances in the mixture (% mass,% volume, molality, and mole fraction) in question number 13 by 99.7% with a very high category. Learning difficulties experienced by students are caused by students not interested, unmotivated, and not talented on stoichiometry material.